Quantum Electrodynamic Modeling of Silicon-Based Active Devices. (11th May 2008) - Shi, Shouyuan; Redding, Brandon; Creazzo, Tim; Marchena, Elton; Prather, Dennis W.
Abstract : We propose a time-domain analysis of an active medium based on a coupled quantum mechanical and electromagnetic model to accurately simulate the dynamics of silicon-based photonic devices. To fully account for the nonlinearity of an active medium, the rate equations of a four-level atomic system are introduced into the electromagnetic polarization vector. With these auxiliary differential equations, we solve the time evolution of the electromagnetic waves and atomic population densities using the FDTD method. The developed simulation approach has been used to model light amplification and amplified spontaneous emission in silicon nanocrystals, as well as the lasing dynamics in a novel photonic crystal-based silicon microcavity.